Motivating the selfish to stop idling: Self-interest cues can improve environmentally relevant driver behaviour. (April 2018) - Van de Vyver, Julie; Abrams, Dominic; Hopthrow, Tim; Purewal, Kiran; de Moura, Georgina Randsley; Meleady, Rose
Highlights: We tested interventions aimed at reducing idling behaviours at long-wait stops. Subtle self-interest cues can significantly reduce idling behaviours. Three types of self-interest (economic, health, kin) are effective. Abstract: Air pollution has a huge and negative impact on society, and idling engines are a major contributor to air pollution. The current paper draws on evolutionary models of environmental behaviour to test whether appeals to self-interest can encourage drivers to turn off their engines at long wait stops. Using an experimental design, drivers were shown one of three self-interest appeals (financial, health, kin) while waiting at a congested level-crossing site in the UK. Results showed that all three self-interest appeals increased the chances of drivers turning off their engines compared to the control condition. Specifically, drivers were approximately twice as likely to turn off their engines in the self-interest conditions (39–41% compliance) compared to drivers in the control condition (22% compliance). Thus, self-interest motives can be effective for promoting pro-environmental behavioural compliance. Theoretical and applied implications of this research are discussed.